2020
DOI: 10.1111/joim.13067
|View full text |Cite
|
Sign up to set email alerts
|

Circulating trimethyllysine and risk of acute myocardial infarction in patients with suspected stable coronary heart disease

Abstract: Background The carnitine precursor trimethyllysine (TML) is associated with progression of atherosclerosis, possibly through a relationship with trimethylamine‐N‐oxide (TMAO). Riboflavin is a cofactor in TMAO synthesis. We examined prospective relationships of circulating TML and TMAO with acute myocardial infarction (AMI) and potential effect modifications by riboflavin status. Methods By Cox modelling, risk associations were examined amongst 4098 patients (71.8% men) with suspected stable angina pectoris. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 38 publications
5
27
2
Order By: Relevance
“…In patients with acute and stable CAD, increased TML levels were associated with higher age, lower GFR and prevalent hypertension (Li et al 2018;Bjornestad et al 2020). We observed similar associations of TML with age and kidney function in acute stroke patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In patients with acute and stable CAD, increased TML levels were associated with higher age, lower GFR and prevalent hypertension (Li et al 2018;Bjornestad et al 2020). We observed similar associations of TML with age and kidney function in acute stroke patients.…”
Section: Discussionsupporting
confidence: 68%
“…Similar to TMAO, increased TML levels were also associated with incident myocardial infarction, MACE and allcause mortality in large prospective cohorts with suspected acute or stable CAD (Li et al 2018(Li et al , 2019Bjornestad et al 2020). In contrast to patients with cardiovascular disease, the prognostic value of TML in patients with acute cerebral ischemia has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study (10) included two independent large cohort, the Cleveland Cohort and the Swiss Cohort, and results showed that patients in the third quartile of TMAO level in the former cohort but not those in the latter cohort presented significant higher cardiovascular risks, which might be due to a higher TMAO level in the former cohort than in the latter one (the third quartile in the former cohort: 4.28-7.89 uM; the third quartile in the latter cohort: 2.87-4.84 uM). Although previous studies reported TMAO as a prognostic biomarker in patients with heart failure, only a few studies (15)(16)(17)38) evaluated TMAO in patients without established heart failure and surprisingly, these studies all reported non-significant prognostic value of TMAO for cardiovascular outcomes after adjustments for traditional parameters. To our knowledge, our study is the first to investigate the role of TMAO in LVSD after a first anterior STEMI and we did not observe a significant relationship between the two.…”
Section: Discussionmentioning
confidence: 97%
“…TMAO is a metabolite derived from gut flora (5) and is related to cardiovascular diseases (6)(7)(8)(9)(10)(11)14). However, its prognostic utility remains controversial, due to different followup intervals (11), study populations (16,17,38), geographical regions (10,39), and ethnicities (40,41). In addition, it has been reported that the core intestinal microbiota in patients with heart failure were usually altered (42), resulting in significantly increased circulating TMAO levels (43).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl groups are derived from the universal methyl donor, S-adenosylmethionine (SAM), an intermediate in the metabolism of the essential sulfur-containing amino acid methionine 2 , ultimately yielding a methylated product and homocysteine (transmethylation). Aberrant methylation patterns and plasma markers of methylation reactions have been associated with progression of metabolic diseases including obesity, cardiovascular disease, and type 2 diabetes mellitus [3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%